DISCUSSING THE CAMPAIGN TO PREVENT GEN Z FORM TO SMOKERS - Pimsarn, Nopphadol; Jongsuksomsakul, Panida; Satjaharuthai, Kriangkrai (Journal of Buddhist Anthropology, 2022)
The campaign to prevent Generation Z to become new smokers has an objective which is to take off the lesson-learned in the campaign to prevent the Generation Z to become a new smoker by using Qualitative Research methods through in-Depth Interview methods and Purposive sampling. This is a campaign to protect the Generation Z from smoking which is carried out by Action on Smoking and Health Foundation Thailand. The results showed that the factors were related to smoking initiation of the new smokers. The factors were family or close friends, friends, advertising of cigarette company. Because of smokers have easily way to access and to purchase of cigarettes in online channel. The principle to prevent the Generation Z is from smoking project. It consists of 5 campaign principles as follows 1) Understanding the problem and planning of the campaign 2) Analyzing the target group 3) Campaign funding 4) Campaign activities and 5) Monitoring and evaluation. Based on cigarette manufacturers' strategy, the project's leading target group is youth between the ages of 7 - 20 years. The key issue contributing to success of the campaign was in a detailed and comprehensive in the campaign. We need to plan consistent with the components which associated with new smoker initiation of smoking. Moreover, it has to combine a variety of communication tools and provide opportunities for the target groups to participate in several steps which encourages the target group to have power and energy to drive this campaign fully. It counted as a “Social Innovation” of driving this campaign to prevent new smokers. However, the future campaign will plan to consider expanding the age of the target group or adjust the strategy of other campaigns currently underway to cover new smokers aged between 19 to 24 to increase the effectiveness of the protection of new smokers in Thailand.